2016
DOI: 10.17583/hse.2016.2299
|View full text |Cite
|
Sign up to set email alerts
|

Seeking new paradigms in Aboriginal education research: methodological opportunities, challenges and aspirations

Abstract: It is only relatively recently that Aboriginal peoples in Australia are represented in the academe, creating knowledges that speak for, and not of us. Internationally renowned Maori scholar, Professor Linda Tuhiwai Smith, was groundbreaking in her use of critical discourses needed for indigenous peoples globally to reclaim our knowledges and experiences through research. The emergence of Aboriginal and Torres Strait Islander scholars in Australia presents hope and opportunities for our communities to utilise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…(p. 72) Universities, as institutionalised systems of knowledge transmission and production, have historically -and in many cases continually -failed to accurately represent, and be governed by, diverse Indigenous Knowledges, pedagogies, and practices (Andersen & Kukutai, 2016;Bodkin-Andrews & Carlson, 2013;Moodie, 2019;Rigney, 2017). Whilst there has been considerable recognition of the changing landscape of Indigenous Studies within the higher education sector (Nakata, 2013;Shay, 2016;Tallbear, 2016), Narungga scholar Rigney (2017) suggests that this progress has been inconsistent, fragmented, and poorly resourced within and across Australian universities.…”
Section: The Indigenisation Of Graduate Attributes?mentioning
confidence: 99%
“…(p. 72) Universities, as institutionalised systems of knowledge transmission and production, have historically -and in many cases continually -failed to accurately represent, and be governed by, diverse Indigenous Knowledges, pedagogies, and practices (Andersen & Kukutai, 2016;Bodkin-Andrews & Carlson, 2013;Moodie, 2019;Rigney, 2017). Whilst there has been considerable recognition of the changing landscape of Indigenous Studies within the higher education sector (Nakata, 2013;Shay, 2016;Tallbear, 2016), Narungga scholar Rigney (2017) suggests that this progress has been inconsistent, fragmented, and poorly resourced within and across Australian universities.…”
Section: The Indigenisation Of Graduate Attributes?mentioning
confidence: 99%
“…In summary, through data analysis and the understanding and reflection of the various narratives, the research process was clarified (Shay 2016). The principal curriculum leadership established a practical framework for the alternative schools for Taiwanese aborigines with the two systems of "belief change" and "structural innovation" and then gradually formed the research scheme shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Indigenous people in Australia, as elsewhere, have been the subject of disempowering, dehumanising and highly negative research discourse (Shay, 2016). Indeed, Tuck (2009, p. 409) argues that these flawed research approaches have inflicted considerable damage by ensuring Indigenous subjects and communities undergo a subjectivity that "reinforces and re-inscribes a one-dimensional notion of these people as depleted, ruined, and hopeless."…”
Section: The Decolonising Waltzmentioning
confidence: 99%
“…While the NHMRC guidelines attempt to subvert the worst excesses of colonisation, in many respects they appear to reinforce them. Shay (2016) notes that the guidelines themselves are written from a non-Indigenous perspective. The 'othering' that is apparent in the text and the vague allusions to Indigenous research methodologies as a consequence of the guidelines being framed in a non-Indigenous framework means these guidelines are problematically applied to contexts where Indigenous researchers are conducting research or those who have positionalities within a transdisciplinary or cross-cultural space (Shay, 2016).…”
Section: Reflections On the Misstepsmentioning
confidence: 99%
See 1 more Smart Citation